Examining benign and malicious envy and flourishing among Muslim university students in Algeria: a quantitative study - Sabah, Aiche; Aljaberi, Musheer A.; Hassan, Siti Aishah (Elsevier, 2025)
Envy is a social emotion that arises from comparing ourselves to others, and it can significantly affect our flourishing in competitive environments such as universities. In Muslim societies, where cultural and religious values emphasize contentment and avoiding harmful emotions, envy's impact may differ. Understanding how harmless and harmful envy can affect students' flourishing is important, as this emotion can either motivate personal growth or hinder it. Therefore, this study aimed to explore how benign and malicious envy influence the flourishing of university students in Muslim society. A cross-sectional design was employed, and data were collected from a sample of 401 Algerian university Muslim students (86.5% female, mean age 21.63 years) from the University of Chlef, with varied economic backgrounds and academic levels ranging from first-year undergraduates to doctoral students. The study utilized the Benign and Malicious Envy Scale and the Flourishing Scale. Multiple regression analysis revealed that benign envy was a significant positive predictor of flourishing, while malicious envy had a significant negative effect. The regression model indicated that only the academic year significantly impacted flourishing, while gender, age, and economic status did not significantly predict flourishing. In terms of benign and malicious envy, gender, age, family economic status, and academic year did not significantly impact either. In conclusion, this study emphasizes the complex impact of envy on people's flourishing, highlighting the different effects of benign and malicious envy. It suggests that fostering benign envy could help individuals thrive while reducing malicious envy, which is important for improving flourishing. The findings offer important insights for educators and policymakers aiming to support students in academic settings, especially in Muslim societies.